Autologous stem cell transplantation in the treatment of systemic sclerosis: report from the EBMT/EULAR Registry. Issue 8 (12th July 2004) - Farge, D; Passweg, J; van Laar, J M; Marjanovic, Z; Besenthal, C; Finke, J; Peter, H H; Breedveld, F C; Fibbe, W E; Black, C; Denton, C; Koetter, I; et al.
Abstract : Objective: To analyse the durability of the responses after haematopoietic stem cell transplantation (HSCT) for severe systemic sclerosis (SSc) and determine whether the high transplant related mortality (TRM) improved with experience. This EBMT/EULAR report describes the longer outcome of patients originally described in addition to newly recruited cases. Methods: Only patients with SSc, treated by HSCT in European phase I–II studies from 1996 up to 2002, with more than 6 months of follow up were included. Transplant regimens were according to the international consensus statements. Repeated evaluations analysed complete, partial, or non-response and the probability of disease progression and survival after HSCT (Kaplan-Meier). Results: Given as median (range). Among 57 patients aged 40 (9.1–68.7) years the skin scores improved at 6 (n = 37 patients), 12 (n = 30), 24 (n = 19), and 36 (n = 10) months after HSCT (p<0.005). After 22.9 (4.5–81.1) months, partial (n = 32) or complete response (n = 14) was seen in 92% and non-response in 8% (n = 4) of 50 observed cases. 35% of the patients with initial partial (n = 13/32) or complete response (n = 3/14) relapsed within 10 (2.2–48.7) months after HSCT. The TRM was 8.7% (n = 5/57). Deaths related to progression accounted for 14% (n = 8/57) of the 23% (n = 13/57) total mortality rate. At 5 years, progression probability was 48% (95% CI 28 to 68) and the projected survival was 72% (95% CI 59 to 75). Conclusion: This EBMT/EULAR report showed that response in two thirds of the patients after HSCT was durable with an acceptable TRM. Based on these results prospective, randomised trials are proceeding.